2008
DOI: 10.1016/j.scr.2008.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of myocardial infarct size by human mesenchymal stem cell conditioned medium

Abstract: Although paracrine effects of mesenchymal stem cells (MSCs) have been suggested previously, cardioprotection by human MSC secretions has never been demonstrated. Human MSC-conditioned medium (CM) was collected by following a clinically compliant protocol. In a porcine model of ischemia and reperfusion injury, intravenous and intracoronary MSC-CM treatment significantly reduced myocardial nuclear oxidative stress as determined by immunostaining for 8-hydroxy-2'-deoxyguanosine. In addition, expression levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
394
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 555 publications
(417 citation statements)
references
References 27 publications
21
394
0
2
Order By: Relevance
“…The most important components within the secretome are the exosomes, which transfer bioactive molecules (such as mRNAs and microRNAs) between cells. 27,28 The exchange of genetic information together with microRNAs leads to reprogramming of recipient cells, allowing them to regenerate damaged tissue. 29,30 In our preclinical studies where human melanoma cells, 9 prostate cancer cells 10 were implanted subcutaneously to immunocompromised nude mice, a significant tumor growth inhibition was observed when suicide gene-engineered MSCs were intravenously injected.…”
Section: Discussionmentioning
confidence: 99%
“…The most important components within the secretome are the exosomes, which transfer bioactive molecules (such as mRNAs and microRNAs) between cells. 27,28 The exchange of genetic information together with microRNAs leads to reprogramming of recipient cells, allowing them to regenerate damaged tissue. 29,30 In our preclinical studies where human melanoma cells, 9 prostate cancer cells 10 were implanted subcutaneously to immunocompromised nude mice, a significant tumor growth inhibition was observed when suicide gene-engineered MSCs were intravenously injected.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it was considered that comparable as in acute GvHD paracrine rather than cellular effects mediate the improvement of cardiac functions following myocardial infarction. Indeed, different labs recovered cardioprotective activities in MSC conditioned media (57)(58)(59). Upon searching for the cardioprotective factors secreted by MSCs, Lee and colleagues identified the anti-inflammatory protein TNF-α-induced protein 6 (TSG-6).…”
Section: Msc In Regenerative Medicinementioning
confidence: 99%
“…These exosomes induce angiogenesis in endothelial cells by direct transfer of mRNA. Timmers L et al [33] demonstrated that media conditioned with hMSC reduce infarct size by 59% in animal model of myocardial ischemia [33].…”
Section: Mechanism Underlying Myocardial Activity Conferred By Stem Cmentioning
confidence: 99%